The impact of initial oral health training on teacher’s knowledge, attitudes, and actions change - Suwargiani, Anne Agustina; Wardani, Riana; Suryanti, Netty; Setiawan, Asty Samiati (Padjadjaran Journal of Dentistry, 2017)
ABSTRACTIntroduction: Formal education is the main place for children to improve their knowledge. Teachers are the sources of information which is easily received by children, so the teacher’s role in children’s education is very important. Oral health training able to improve the skills and information resource in a community. Teachers, as the trainee, can play a role in improving the access to information regarding oral health. The objective of this research was to assess the knowledge, attitude and practice of the teachers before and after the performance of initial training on oral health care. Methods: Questionnaires, with the research variables were knowledge, attitude, and practice of oral health care. The study population was Arraffi Elementary School teachers. The sampling technique was total sampling. The data collecting was done by distributing questionnaires and self-report before and after training. Results: Wilcoxon test shown that P-value pretest and posttest of knowledge was 0.675, attitude was 0.354, and practice was 0.129. Knowledge regarding oral care showed an increasing in achievement percentage. Posttest results of attitude showed the increase in the percentage of positive and negative statements. Posttest results on practice showed some behavior having an increasing percentage, but one behavior remain unchanged. There was no significant difference of knowledge, attitude and practice before and after initial training. Conclusions: There was no impact of initial oral health training on teacher’s knowledge, attitudes, and actions change.Keywords: Knowledge, Attitude, Practice, Teacher, Training